Caries dental asociada al índice de higiene oral simplificado en niños de 6 a 12 años de una institución educativa pública del distrito de Ate – Vitarte en el año 2013 - Moses Augusto, Ana Ximena (2014)
The purpose of this study was to determinate the association between the presence of dental caries and the simplified oral hygiene index for children from 6 to 12 years of a Public School in Ate - Vitarte during 2013. This was a descriptive, observational, cross-sectional and prospective study. The sample consisted of 247 primary students aged from 6 to 12 years old in a public school of Ate – Vitarte district. Diagnosis of oral health was performed by one examiner calibrated under WHO criteria (kappa =0.08), using a mouth mirror and periodontal probe. The prevalence of dental caries was measured by the presence or absence of disease, while for dental caries experience DMFT and dmft index were used. Simplified oral hygiene index (OHI) of Greene and Vermillon was used for the diagnosis of oral hygiene. The Chi-square, Kruskal Wallis and Mann Whitney U tests were used for statistical analysis of the data obtained. Prevalence of dental caries was 92.71 % , DMFT and dmft of all evaluated children were 1.51 and 5.57 respectively. The simplified oral hygiene index showed that 34.82% of children had good oral hygiene, while 57.49% had regular hygiene and finally 7.69% had poor oral hygiene. A statistically significant association (p =0.000) between the presence of dental caries and oral hygiene index simplified was found. This research reaffirms the known concepts in the published scientific evidence, and presents the state of oral health of the children living in a district of the capital of the country, guiding their results to develop a strategic plan and dental work a monkey reo ¬ appropriate to reduce this disease.